2019
DOI: 10.1038/s41598-019-54785-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical investigation of extragraft bone formation influences on the operated motion segment after anterior cervical spinal discectomy and fusion

Abstract: Although the clinical importance of extragraft bone formation (ExGBF) and bridging (ExGBB) has been reported, few studies have investigated the biomechanical influences of ExGBF on the motion segment. In this study, ExGBF was simulated at the C5-C6 motion segment after anterior cervical discectomy and fusion using a developed finite element model and a sequential bone-remodelling algorithm in flexion and extension. The computer simulation results showed that extragraft bone was primarily formed in the extensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…They found that the average change in interbody force magnitude from full extension to full flexion decreased significantly during fusion. Furthermore, Park and Jin (2019 ) and Jin and Park (2021 ) simulated extragraft bone formation at the C5–C6 motion segment after ACDF using a developed finite element model and a sequential bone-remodeling algorithm in flexion and extension. The results suggested that both the stress and strain energy density slightly changed in flexion while a significantly stepwise decrease was predicted in extension until the fusion was terminated ( Park and Jin, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the average change in interbody force magnitude from full extension to full flexion decreased significantly during fusion. Furthermore, Park and Jin (2019 ) and Jin and Park (2021 ) simulated extragraft bone formation at the C5–C6 motion segment after ACDF using a developed finite element model and a sequential bone-remodeling algorithm in flexion and extension. The results suggested that both the stress and strain energy density slightly changed in flexion while a significantly stepwise decrease was predicted in extension until the fusion was terminated ( Park and Jin, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Park and Jin (2019 ) and Jin and Park (2021 ) simulated extragraft bone formation at the C5–C6 motion segment after ACDF using a developed finite element model and a sequential bone-remodeling algorithm in flexion and extension. The results suggested that both the stress and strain energy density slightly changed in flexion while a significantly stepwise decrease was predicted in extension until the fusion was terminated ( Park and Jin, 2019 ). Therefore, more attention should be paid to the stress distribution of interbody implant in extension because of the significant changes during fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, degenerative and traumatic diseases are observed most frequently in the motion segment [17,18], and it was chosen to simulate extragraft bone formation in this study. A validated finite element (FE) model of the osteoligamentous C5-C6 motion segment was used ( Figure 1) [19], which was developed using anonymised computed tomographic images collected from the Catholic Digital Human Library (Approval No. CUMC10U161, IRB, College of Medicine, The Catholic University of Korea).…”
Section: Finite Element Model Of the Operated C5-c6 Motion Segmentmentioning
confidence: 99%
“…The movements and the axial pre-compression forces were loaded onto L3. By using frictionless contact, the facet joints were simulated [12]. To verify the intact model, a comparison of the predicted results with those reported in the literature was performed.…”
Section: Fe Modeling and Validationmentioning
confidence: 99%